OPINION OF THE ZAKAH RECIPIENTS ABOUT THE ROLE OF ZAKAH ON THE HOUSEHOLD FOOD SECURITY: EVIDENCE FROM THE RURAL BANGLADESH - Tarique, Kazi Md.; Mahmud, Kazi Tanvir; Hasan, Md. Kamrul (Bank Indonesia, 2016)
All economically solvent muslims according to the eligibility yardstick of giving zakah, are oblized to pay zakah. Payment of zakah is to distribute a certain part of once wealth among the poor, as per the Islamic philosophy, so that the poor can graduate from poverty utilizing this zakah fund. The prime objective of this study is to assess the opinion of the zakah recipients about the impact of zakah funds on their living- standard in terms of food security. Logit model is used to assess the opinion of the zakah recipients on their food security status. The study found no significant impact of zakah fund on the food security of some selected receipents in the rural areas of Bangladesh.